Mass Customization in Industrial Housing Production - Sariyar, Altug; Pakdil, Oya (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2012)
Beginning in the mid-20th Century, consumer-oriented production approaches replaced early attitudes towards mass production and helped mass customization move forward. Through the widespread use of information technologies, the mass-customization approach aimed to position the consumer and his/her preferences directly in line with production processes with the help of consumer participation methods and product configuration tools. In this study, the house as a product system, consisting of related sub-systems within a housing market, is being researched as a consumer product which may be customized in the pre-occupancy stage with the help of the mass-customization approach. To do that, adaptability and user participation approaches must be discussed. Then the mass-customization approach is adapted in the housing industry as a tool for adaptability. The field study has focused on the mass-customization approach used in the production processes of high-end multi-story housing in Istanbul. In order to research the level of mass customization used in these housing areas, two surveys have been conducted. The first of these was given to the construction firms, the second to potential buyers. The results were discussed, and suggestions were generated. With the help of the data obtained, it has become clear that in the building and housing industry, consumer-oriented production and mass-customization approaches are improving and providing potential for adaptability. The results also confirm that, for the time being, the mass-customization approach of the producers is mainly used for providing variety and adaptability on the finishing and equipment levels, despite the fact that most of survey participants have customization expectation on the spatial organization level.
Keywords: Mass production; user centered design; mass customization; consumer oriented industrialization in housing production; Architecture